2008
DOI: 10.1080/13693780701636567
|View full text |Cite
|
Sign up to set email alerts
|

Fournier's gangrene due toCandida glabrata

Abstract: Fournier's gangrene is a rare and serious event. Usual pathogens are bacteria of the skin and the digestive tract. Candida species are exceptionally involved, mostly Candida albicans. We report a patient with non-C. albicans Candida sp. Fournier's gangrene who survived with an appropriate antifungal therapy. Yeasts should be considered as emerging pathogens in pelvic infections due to the increase in long-term immunocompromised patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 13 publications
0
12
0
2
Order By: Relevance
“…However, single-case reports describing FG caused by fungi are reported. C. albicans , Candida glabrata and Rhisopus microsporus etiology are described in adults [5, 10, 11]. Our case report is unique because to the best of our knowledge there is no report of solitary C. albicans FG in children.…”
Section: Discussionmentioning
confidence: 85%
See 4 more Smart Citations
“…However, single-case reports describing FG caused by fungi are reported. C. albicans , Candida glabrata and Rhisopus microsporus etiology are described in adults [5, 10, 11]. Our case report is unique because to the best of our knowledge there is no report of solitary C. albicans FG in children.…”
Section: Discussionmentioning
confidence: 85%
“…The disease mostly affects patients between 50 and 60 years of age, and in children FG is not common. However, FG is a fulminant and life-threatening disease, because although proper treatment mortality in these groups of patients remains high, mortality rates of 7.5–88% are reported [2, 5–8]. A literature review found only <60 pediatric cases of FG worldwide, with 66% of those in infants younger than 3 months [9].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations